Distributed multimedia databases techniques and applications - Shih, Timothy K. 1961- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2002)
In the last few years, we have observed an explosive growth of multimedia computing, communications, and applications. This revolution is transforming the way people live, work, and interact with each other and is impacting the way business, government services, education, entertainment and health care are operating. Yet, several issues related to modeling, specification, analysis and design of distributed multimedia database systems and multimedia information retrieval are still challenging to both researchers and practitioners. This book points out these challenges and provides suggestions toward solutions by focusing on multimedia database techniques